Wayfair: Its Implications and Missed Opportunities - Richard D. Pomp (Washington University Journal of Law & Policy, 2019)
This article reviews the Wayfair decision and its implications. First Professor Pomp considers the term “substantial nexus” which the court used in Quill to distinguish its commerce clause and due process jurisdprudence. He argues the Wayfair court should have used the opportunity to discard the term entirely as it was an invention of the court in Complete Auto that used the term once when the issue was not properly before the court. It then argues Wayfair extends beyond the issue directly in front of it and applies broadly such that taxpayers can no longer avoid state taxes by arguing they lack sufficient nexus with the state. In light of this conclusion the article provides guidance for state tax authorities seeking to collect state taxes in a post-Wayfair world.
Keywords: Tax; SALT; State and local taxes; Tax law; South Dakota v. Wayfair; Inc. 138 S. Ct. 2080 (2018); Quill Corp. v. North Dakota; 504 U.S. 298 (1992); Use tax; Sales tax